Construction and practice of nursing service system in the Traditional Chinese Medicine appropriate technology clinic (中医适宜技术门诊护理服务体系的构建与实践) - DAI Yuanhua (戴远华); GUO Jing (郭敬); WANG Ying (王颖) (Journal of International Translational Medicine Limited, 2022)
This paper explore the construction and practice of nursing service system in the Traditional Chinese Medicine (TCM) appropriate technology clinic. TCM appropriate technology clinic, as an independent nursing unit, explores the management mode, hardware facilities and equipment configuration and environment construction, nursing personnel configuration, service items, quality control, and cooperative departments, and develops the nursing service system. The construction and application of TCM appropriate technology clinic nursing service system has expanded the service scope for nursing personnel to implement TCM appropriate technology, met the needs of outpatients for TCM appropriate technology, promoted the improvement of TCM nursing service capacity, and provided reference for the construction of TCM nursing outpatient service system. (本文探讨了中医适宜技术门诊护理服务体系的构建及应用效果。中医适宜技术门诊作为独立的护理单元, 从管理模式、诊室硬件设施设备配置及环境建设、护理人员配置、服务项目、质量监控、合作科室6个方面进行探索, 制定中医适宜技术门诊护理服务体系。医院中医适宜技术门诊护理服务体系的构建和应用, 拓展了护理人员实施中医适宜技术的服务范围, 满足了门诊患者对中医适宜技术的需求, 促进了中医护理服务能力的提升, 可为中医护理门诊服务体系建设提供参考。)